Microbialitic deposits of the Yacoraite Formation, NW Argentina: distribution, environments, paleoecology, and economic implications - Villafañe, Patricio Guillermo (2022)
The Yacoraite Formation (NW Argentina) displays important microbialitic deposits of varied features throughout its six sub-basins. With the discovery of important microbialitic hydrocarbon reservoirs and the interest in lacustrine systems due to recent hydrocarbon finds in the pre-salt Cretaceous series of the South Atlantic, the importance of these organo-sedimentary structures has increased considerably. Because of this, in the past decade, numerous works in Yacoraite Formation have focused on its microbialites. In this study, we provide an updated summary of the existing background and state of knowledge of the microbialites in the Yacoraite Formation, which occupy different stratigraphic positions in diverse sub-basins separated by several kilometers. Due to this, these structures have developed under diverse conditions, giving rise to a great variety of structures and morphologies, useful as reliable and high-resolution proxies for paleoenvironmental studies and to discuss important ecological paradigms. In addition, microbialites of Yacoraite Formation show promising petrophysical conditions to be evaluated as reservoir rocks. Based on the large number of deposits mentioned throughout this work, and the morphological and structural variety of their microbialites, we can highlight Yacoraite Formation as one of the most important microbialite-bearing units in Argentina and South America.